The Effect of Single or Combined Dietary Supplementation of Mannan Oligosacharide and Probiotics on Performance and Slaughter Characteristics of Broilers - Abdel-Raheem , Sherief M.; Abd-Allah, Sherief M.S. (International Journal of Poultry Science, 2011)
A feeding trial was conducted to investigate the effects of dietary supplementation of prebiotic (mannan oligosaccharide, MOS), Probiotic (Saccharomyces cerevisiae) and their combination (synbiotic) on growth performance, some carcass traits and meat quality in broilers. One hundred, one day-old broiler chicks (Avian 48), were randomly assigned to 4 dietary treatments (25 birds/treatment) for 6 weeks. Treatment groups were as follow: 1. Basal diet (control); 2. Basal diet plus Mannan-Oligosaccharide (MOS) (2 g of MOS/kg of the starter diets and 0.5 g/kg of the grower diets); 3. Basal diet plus probiotic (Saccharomyces cerevisiae) 3 g/kg diet and 4.Basal diet plus the combination of pre and probiotics (synbiotic). The final BW, weight gain, carcass yield percentage and immune organ weights were significantly (p